Introduction to the Special Issue on Corporate Social Reporting In Central and Eastern Europe - Cătălin Nicolae Albu; Cagnur Kaytmaz Balsari; Joanna Krasodomska (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Corporate Social Responsibility (CSR) regulations, frameworks and practices have increasingly preoccupied accounting researchers over the last decades. The countries in Central and Eastern Europe (CEE) have significantly evolved after the fall or the decline of their non-democratic regimes, and improved reporting by companies in such countries is called for and supported by international and regional organizations, as well as driven more or less successfully by local bodies. In the midst of such evolutions, CSR-related matters are an important concept materializing in the accounting academic and practitioner literature in the CEE region, as well as in the practices of local companies. We then devote this special issue of the Journal of Accounting and Management Information Systems to studying the state of CSR reporting in the CEE region. We include in this special issue six papers that treat the respective cases of Poland, Romania and Turkey as exponents of the CEE region. Results of the papers published attest to the increased interest showed by accounting researchers in the CEE region to CSR-related matters. However, a number of issues still require further investigation, such as the determinants and consequences of good CSR practices, the process of change in integrating the CSR thinking in organizations, CSR disclosures and the impact of the institutional context, the role of regional and national regulators in establishing adequate CSR regulations and frameworks that promote sound CSR practices in the region, the perception of CSR-related matters by the millennials, or the impact of Information Technology advancements on CSR practices.
Keywords: M14; M40; Q56; 650; Corporate Social Responsibility; Central and Eastern Europe; CSR reporting